Association between sleep quality and sleep paralysis in medical students from a private university in Paraguay - Coronel-Ocampos, Johanna Magalí (2020)
Background: The influence of sleep quality in sleep paralysis has not been widely documented in medical students, although they are exposed to high academic loads in undergraduate studies. Aim: To determine the association between sleep quality and paralysis in medical students from Paraguay. Methods: Analytical cross-sectional study in first- and second-year medical students at Universidad del Pacífico, Paraguay in 2018. The questionnaire was self-administered and consisted of socio-educational data (age and sex), index of Pitsburgh sleep quality and self-reported sleep paralysis. Simple and multiple regression models were built, estimating prevalence ratios. Results: Of 329 medical students, the majority were male (34.7%) and the median age was 19 years. 48.3% and 47.1% presented poor quality of sleep and sleep paralysis; respectively. Poor sleepers had a 40% higher frequency of reporting sleep paralysis (PR = 1.40). Men had a 28% lower frequency of reporting sleep paralysis (PR = 0.72). For each additional year of age, the frequency of sleep paralysis decreased 14% (PR = 0.86). Conclusion: Almost half were poor sleepers and suffered from sleep paralysis. Our findings suggest that there is a positive association between quality and sleep paralysis. Additionally, sex and age were also factors associated with a higher frequency of sleep paralysis in medical students.